Strengthening the Religious Moderation through Innovation of Islamic Religious Education (IRE) based Civic Intelligence and the Values Clarification Technique (VCT) - Thoriquttyas, Titis; Saputra, Meidi; Huda, Imamul; Hanafi, Yusuf; Zaimatus, Nila (KnE Social Sciences, 2020)
In Indonesia, the dissemination of religious radicalism not only occurs in educational institutions but has also spread into other social institutions. In the scope of higher education, the National Counter Terrorism Agency (BNPT) released the results of their research in 2018, indicate the emergence of radicalism in several state universities. Although several other parties questioned the details of BNPT’s findings, the research made “politics of fear” after explicitly labelling seven well-known state universities exposed to radical ideology. This research is directed to formulate the learning innovation on Islamic Religious Education (IRE) based Civic Intelligence using the Values Clarification Technique (VCT) learning model as an effort to strengthen religious moderation. This research is classified into the research and development (R&D) model which conducted at State University of Malang (UM) and the development model used the ADDIE model. The result revealed that the mapping for religious moderation after getting treatment can be grouped into five categories (very high: 9.97%, high: 9.30%, moderate: 51.82%, low: 26.57% and very low: 2.32%). Keywords: Civic Intelligence, Moderation, Islamic Religious Education